2005
DOI: 10.1385/endo:27:2:179
|View full text |Cite
|
Sign up to set email alerts
|

Putting Cancer to Sleep at Night: The Neuroendocrine/Circadian Melatonin Signal

Abstract: Physiological and pharmacological blood concentrations of melatonin inhibit tumorigenesis in a variety of in vivo and in vitro experimental models of neoplasia. Evidence indicates that melatonin's anticancer effects are exerted via inhibition of cell proliferation and a stimulation of differentiation and apoptosis. A new mechanism by which physiological and pharmacological blood levels of melatonin inhibit cancer growth in vivois via a melatonin-induced suppression of tumor linoleic acid (LA) uptake and its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
157
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(167 citation statements)
references
References 37 publications
3
157
1
5
Order By: Relevance
“…Chronic melatonin suppression has been linked to both initiation and promotion of cancer because melatonin is a hormone with oncostatic properties (4,6,36,37). However, the anticancer effects of melatonin depend on the circadian stage, as suggested by animal studies (reviewed in ref.…”
Section: <0001mentioning
confidence: 99%
“…Chronic melatonin suppression has been linked to both initiation and promotion of cancer because melatonin is a hormone with oncostatic properties (4,6,36,37). However, the anticancer effects of melatonin depend on the circadian stage, as suggested by animal studies (reviewed in ref.…”
Section: <0001mentioning
confidence: 99%
“…In addition to protecting DNA by suppressing the formation and accumulation of altered DNA, melatonin may also help to promote DNA repair (15,(91)(92)(93).…”
Section: Melatonin Suppression By Light At Nightmentioning
confidence: 99%
“…Growth-inhibitory and oncostatic properties of melatonin have been well described (reviewed in ref. 30). Several in vitro studies have reported a reduction in the growth of malignant cells and/or tumors of the breast (31)(32)(33)(34)(35) prostate (36)(37)(38)(39)(40)(41), and other tumor sites (42)(43)(44)(45)(46) by both pharmacologic and physiologic doses of melatonin.…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%